Effects of electroacupuncture on central insulin signal transduction-related proteins in insulin resistance model rats via the mTORC1/S6K1 pathway - Xiu-feng GU; Jing-zhi WANG; Ming KONG; Li CHEN; Jie SONG; Tao QU (World Journal of Acupuncture - Moxibustion)
Objective: To investigate the effects of electroacupuncture (EA) on the expression and phosphorylation of insulin signal transduction-related proteins in the hypothalamus of insulin resistance (IR) rats. Methods: There were totally seventy-five Wistar rats. Ten rats were randomly assigned to the Normal group (N).The remaining 65 rats were fed a high-fat diet, fifty successfully modeled rats were randomly divided into the Model (M), EA, Sham EA (S+EA), l-leucine (L), and l-leucine + EA (L+EA) groups, with 10 rats in each group.EA was applied at acupoints “Guanyuan (CV 4)”, “Zhongwan (CV 12)”, “Zusanli (ST 36)”, and “Fenglong (ST 40)”, with each session lasting 10 min, three times per week for 8 weeks. The S+EA group received needle insertion to a depth of ≤2 mm without electrical stimulation, with the same treatment duration and same acupoint selection. Body weight, fasting blood glucose (FBG), and insulin sensitivity (glucose infusion rate, GIR) were measured. Western blot analysis was used to assess insulin receptor substrate-1(IRS-1) , (Protein kinase B)Akt, glycogen synthase kinase-3β(GSK-3β),mechanistic target of rapamycin complex 1(mTORC1), and Ribosomal S6 kinase 1(S6K1), along with their phosphorylated forms. PCR was used to evaluate mRNA expression of IRS-1, Akt, and GSK-3β. Immunofluorescence was used to detect hypothalamic Akt localization. Results: (1) Compared to the N group, the M group exhibited increased body weight, FBG, and phosphorylation of GSK-3β, mTORC1, and S6K1, with decreased GIR, IRS-1, Akt phosphorylation, and mRNA expression (P < 0.05, P < 0.01). (2) Compared to the M group, the EA and S+EA groups showed reduced body weight, FBG, GSK-3β, mTORC1, and S6K1 phosphorylation, with increased GIR, IRS-1, Akt phosphorylation, and mRNA expression (P < 0.05, P < 0.01). (3) Compared to the EA group, the S+EA group had higher body weight, GSK-3β phosphorylation, and mRNA expression, with reduced p-IRS-1 and p-Akt expression (P < 0.05); the L and L+EA groups showed increased GSK-3β, mTORC1, and S6K1 phosphorylation, with decreased GIR, IRS-1, and Akt mRNA expression (P < 0.05). (4) Compared to the L+EA group, the L group exhibited higher GSK-3β, mTORC1, and S6K1 phosphorylation, with lower GIR, Akt mRNA, and p-Akt expression (P < 0.05, P < 0.01). Conclusion: EA positively influences body weight, glucose-lipid metabolism, and insulin sensitivity in IR rats, with regulatory effects on central insulin signal transduction-related proteins, potentially linked to its suppression of hypothalamic mTORC1/S6K1 pathway activity.